NEW OCCURRENCE OF TWO EXOTIC HYDROPHYTES AZOLLA FILICULOIDES LAM. AND HYDRILLA VERTICELLATA (L. F.) ROYLE IN TIGRIS RIVER WITHIN MOSUL CITY - basheer Al-Nimaa; Fathi Al-Mandeel; Fathi Al-Mandeel (Mesopotamia Journal of Agriculture)
The present research is a scientific documentation of a historical environmental event, which is the invasion of two species of non-native (exotic) aquatic plants for the Tigris River flowing in Mosul city center near Al-Dandan water purification plant. One of them is Azolla filiculoides Lam., a fern belonging to the family Salviniaceae, the other being Hydrilla verticellata (L. f.) Royle, a monocotyledons plant belonging to the family Hydrocharitaceae. The most important morphological characteristics of both species’ vegetative parts enable their identification. Morphological examination of H. verticellata leaf, revealed that it is monoecious biotype like that found in the states of America which are located in the northern latitudes, and not dioecious like the type found in southern latitudes states. It is recommend from the relevant specialists to monitor these two species and study the possibility of their conversion to invasive plants, It is also recommended from them   to studying their impacts on the aquatic life of the river. Aim of the present study is to document the invasion of two alien hydrophytes to Tigris river that flow within Mosul city, North of Iraq.